2015
DOI: 10.1371/journal.pone.0126510
|View full text |Cite
|
Sign up to set email alerts
|

Computational Docking Study of p7 Ion Channel from HCV Genotype 3 and Genotype 4 and Its Interaction with Natural Compounds

Abstract: BackgroundThe current standard care therapy for hepatitis C virus (HCV) infection consists of two regimes, namely interferon-based and interferon-free treatments. The treatment through the combination of ribavirin and pegylated interferon is expensive, only mildly effective, and is associated with severe side effects. In 2011, two direct-acting antiviral (DAA) drugs, boceprevir and telaprevir, were licensed that have shown enhanced sustained virologic response (SVR) in phase III clinical trial, however, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 86 publications
(79 reference statements)
2
5
0
Order By: Relevance
“…61,62 Molecular docking analysis also found that Que may interact with HCV NS3 helicase, NS5B polymerase, and p7 proteins. 63,64 These results correlate with experimental studies showing the anti-HCV activity of Que through inhibition of NS3 helicase and heat-shock proteins. [65][66][67] A phase I trial investigated the potential antiviral effect of Que among patients with hepatitis C virus (HCV).…”
Section: Beneficial Effects Of Que In Viral Infectionssupporting
confidence: 80%
“…61,62 Molecular docking analysis also found that Que may interact with HCV NS3 helicase, NS5B polymerase, and p7 proteins. 63,64 These results correlate with experimental studies showing the anti-HCV activity of Que through inhibition of NS3 helicase and heat-shock proteins. [65][66][67] A phase I trial investigated the potential antiviral effect of Que among patients with hepatitis C virus (HCV).…”
Section: Beneficial Effects Of Que In Viral Infectionssupporting
confidence: 80%
“…In addition, in silico analysis revealed that quercetin may be a potential inhibitor of the neuraminidase of influenza A H1N1 and H7N9 viruses [79,80]. Molecular docking analysis also found that quercetin may interact with HCV NS3 helicase, NS5B polymerase and p7 proteins [34,86]. These results correlate with experimental studies showing the anti-HCV activity of quercetin through inhibition of NS3 helicase and heat shock proteins [4,81].…”
Section: Antiviral Activity Of Flavonolssupporting
confidence: 75%
“…Some 3a-inhibitory kaempferol derivatives were identified, the glycoside juglanin being the most efficient ( Schwarz et al, 2014 ). A computational docking study of p7 ion channel from HCV Genotype 3 and Genotype 4 tested different flavonoids including Epigallocatechin-3-gallate, apigenin, naringenin, luteolin, quercetin, ladanein, silymarin, honokiol, and nobiletin, showing the existence of flavonoid binding pockets in different viroporins ( Mathew et al, 2015 ). Our results identify quercetin and EGCG as potential ligands and inhibitors of the SARS-CoV E protein.…”
Section: Discussionmentioning
confidence: 99%